The Financial Feasibility Study of N219 Aircraft in Papua - Lubis, Aliananda; Surya, Budhi Arta (Journal of Business and Management, 2014)
The Republic of Indonesia has the largest archipelago in the world. With the geographical condition, however, there are still several areas that are isolated and difficult to reach, even not accessible by road. These conditions will make it difficult for the Government in an effort to build connectivity between areas in an attempt to equitable development. PT. Dirgantara Indonesia or known as Indonesian Aerospace (IAe) is developing a new aircraft, which is suitable for the mission of the pioneer air transportation. The aircraft is the N-219, which has capacity to carry 19 passengers and cargos and will entry into service in year 2017. The aircraft route that will be discussed specifically in this study is based in Timika, Mimika Regency, Papua. The total project cost and the revenue will determine the project calculation. Then the cost and the revenue will be used to calculate the Net Present Value (NPV), Internal Rate of Return (IRR), and as well as Payback Period (PBP). After all of the calculation is done, then the calculation of the Sensitivity Analysis will be made. Then, the result of the calculation which are NPV, IRR, and PBP will show the project whether it is feasible or not. This final project presents to readers a clearly vision of financial production of a turboprop aircraft. It will also help the potential airlines, which may be interested on buying this kind of aircraft in the future. As for the conclusion, the NPV of the project is USD 37,004,404.- , the IRR is 27.3% (which good because its greater than the Minimum Acceptable Rate of Return), the Payback Period is 5 years 4 months (which is also good enough because it is still during the project lifetime). So from these results, it can be concluded that this project is feasible.Â Keywords: Aviation Routing, Feasibility Study, Sensitivity Analysis